An overview of activity-based probes for glycosidases. (December 2019) - Wu, Liang; Armstrong, Zachary; Schröder, Sybrin P; de Boer, Casper; Artola, Marta; Aerts, Johannes MFG; Overkleeft, Herman S; Davies, Gideon J
Highlights: Glycosidases carry out many essential functions across all domains of life. Activity-based probes can interrogate complex biological samples for glycosidase activity. Glycosidase probes can characterize enzymes of biomedical/biotechnological interest. Analysis of conformational itineraries may inform the design of future probes. Activity-based probes assist high-throughput discovery of inhibitors. Abstract : As the scope of modern genomics technologies increases, so does the need for informative chemical tools to study functional biology. Activity-based probes (ABPs) provide a powerful suite of reagents to probe the biochemistry of living organisms. These probes, featuring a specificity motif, a reactive chemical group and a reporter tag, are opening-up large swathes of protein chemistry to investigation in vitro, as well as in cellular extracts, cells and living organisms in vivo . Glycoside hydrolases, by virtue of their prominent biological and applied roles, provide a broad canvas on which ABPs may illustrate their functions. Here we provide an overview of glycosidase ABP mechanisms, and review recent ABP work in the glycoside hydrolase field, encompassing their use in medical diagnosis, their application for generating chemical genetic disease models, their fine-tuning through conformational and reactivity insight, their use for high-throughput inhibitor discovery, and their deployment for enzyme discovery and dynamic characterization.